1984
DOI: 10.1021/bi00303a016
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of isoleucine in methanogenic bacteria: a carbon-13 NMR study

Abstract: The biosynthesis of isoleucine by seven species of methanogenic bacteria was studied by using 13C NMR, following growth in media containing specifically 13C-labeled compounds. It was found that in these bacteria a-ketobutyrate is not derived from threonine. In all cases, when acetate and C 0 2 serve as the total carbon sources, the labeling pattern of isoleucine is consistent with the operation of the pyruvate Published 1984 by the American Chemical Society Crit. Rev. Environ. Control 4 , 131-191. 1195-1203. 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
24
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 25 publications
4
24
0
Order By: Relevance
“…Some anaerobes can assimilate 2-methylbutyrate into isoleucine (33). In some pseudorevertants of ilvA mutants, ␣-ketobutyrate can arise from precursors other than threonine (3,6,9,11,13,14,15,30,39,41). Of the latter, the most commonly observed was a route from pyruvate and acetyl coenzyme A (acetyl-CoA) via citramalate (3,9,39,41).…”
mentioning
confidence: 99%
“…Some anaerobes can assimilate 2-methylbutyrate into isoleucine (33). In some pseudorevertants of ilvA mutants, ␣-ketobutyrate can arise from precursors other than threonine (3,6,9,11,13,14,15,30,39,41). Of the latter, the most commonly observed was a route from pyruvate and acetyl coenzyme A (acetyl-CoA) via citramalate (3,9,39,41).…”
mentioning
confidence: 99%
“…While 13C-labeling studies of whole cells of methanogenic archaebacteria have provided evidence for the common pathway, only the properties of the methanococcal AHAS have been described (11,12,42). The methanococci are marine methanogens which use H2-CO2 or formate as a substrate for methanogenesis (17).…”
mentioning
confidence: 99%
“…The labeling pattern of squalene supported the above conclusions. Based on these data, a general scheme is proposed to account for the contribution of lysine-to-lipid biosynthesis.Our previous papers on the application of the 13C-nuclear magnetic resonance (NMR) technique to study the metabolic pathways of methanogenic bacteria (7,8,10) showed several significant differences in biosynthesis when compared with the biosynthesis of other amino acids by bacteria and eucaryotes. Similar studies for comparison with halobacteria are lacking.…”
mentioning
confidence: 99%